MicroRNAs and Oxidative Stress Markers as Additional Diagnostic Criteria for Coronary Heart Disease - Oksana Yu. Marchenko; Nadiya M. Rudenko; Dmytro S. Krasnienkov (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To examine the significance of microribonucleic acids (miRNAs) and oxidative stress markers in predicting the onset of atherosclerosis and the connection between oxidative stress levels and miRNAs in individuals with coronary heart disease.Materials and methods. Initially, 40 patients were divided as follows: 10 subjects without any lesions in coronary arteries (group 0), 4 patients with non-stenotic atherosclerosis (group 1), and 26 patients with significant multivessel atherosclerotic lesions (group 2). Various biochemical parameters were analyzed, including miRNA expression levels and common oxidative stress markers.Results. The groups were comparable in terms of the patients’ age, but there was unequal distribution of males and females in the angio-groups as per Fisher’s exact test. We also analyzed the data separately for females, but no significant difference was found. There were significant differences in miRNA-122 levels, N-terminal prohormone of brain natriuretic peptide levels, lipid profiles, and oxidative stress markers between group 0 and groups with atherosclerotic lesions. Specifically, miRNA-122 levels were elevated in group 0, along with N-terminal prohormone of brain natriuretic peptide, triglycerides, ratio of triglycerides to high-density lipoprotein cholesterol, and oxidative stress markers. Conversely, compared to group 0, total cholesterol, high-density lipoprotein cholesterol, bilirubin, and specific glutathione levels decreased in patients with coronary lesions.Conclusions. The study demonstrated the potential of miRNAs, particularly miRNA-122, as predictive biomarkers for atherosclerosis. Further research with larger cohorts is warranted to validate these findings and explore additional miRNA candidates and therapeutic interventions for cardiovascular diseases.